PERAN PROFITABILITAS DALAM MEMEDIASI PENGARUH FINANCIAL LEVERAGE DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN DI BURSA EFEK INDONESIA - Sari, Ni Made Dewi Puspita; Wiksuana, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018, 2018)
The purpose of this study was to determine the role of profitability in mediating the effect of financial leverage and investment opportunity set on the dividend policy. The populations in this study were manufacturing companies listed on the Indonesia Stock Exchange. The sampling of the research was done by census and the number of samples were 12 companies. The data of research were secondary data obtained from Indonesia Stock Exchange website and Indonesian Capital Market Directory from 2011 to 2015. Testing of research hypothesis was conducted by using path analysis technique by tool of SPSS application.The results showed that financial leverage has a negative and significant effect on dividend policy. Investment opportunity set has negative and insignificant effect on dividend policy. Financial leverage has a positive and significant impact on profitability. Investment opportunity sets also have a positive and significant impact on profitability. Profitability has a positive and significant effect on dividend policy. Profitability is able to mediate the effect of financial leverage and investment opportunity set on dividend policy.